2020
DOI: 10.3389/fchem.2020.00359
|View full text |Cite
|
Sign up to set email alerts
|

MWCNT-Supported PVP-Capped Pd Nanoparticles as Efficient Catalysts for the Dehydrogenation of Formic Acid

Abstract: Various carbon materials were used as support of polyvinylpyrrolidone (PVP)-capped Pd nanoparticles for the synthesis of catalysts for the production of hydrogen from formic acid dehydrogenation reaction. Among investigated, MWCNT-supported catalysts were the most promising, with a TOF of 1430 h −1 at 80 • C. The presence of PVP was shown to play a positive role by increasing the hydrophilicity of the materials and enhancing the interface contact between the reactant molecules and the catalytic active sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…), and Pd/HTC, respectively). Such a positive effect of nitrogen in attaining good catalytic performance in the dehydrogenation of formic acid has been attributed to both the participation of nitrogen atoms in the reaction by interacting with formic acid molecules and increasing the local concentration close to the Pd active sites and the role of nitrogen in modifying the electronic properties of Pd atoms. ,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…), and Pd/HTC, respectively). Such a positive effect of nitrogen in attaining good catalytic performance in the dehydrogenation of formic acid has been attributed to both the participation of nitrogen atoms in the reaction by interacting with formic acid molecules and increasing the local concentration close to the Pd active sites and the role of nitrogen in modifying the electronic properties of Pd atoms. ,, …”
Section: Resultsmentioning
confidence: 99%
“…Such positive effect of nitrogen in attaining good catalytic performance in the dehydrogenation of formic acid has been attributed to both the participation of nitrogen atoms in the reaction by interacting with formic acid molecules and increasing the local concentration close to the Pd active sites, and the role of nitrogen in modifying the electronic properties of Pd atoms. 26,50,51 This latest effect can be checked by analyzing XPS results included in Figure 4. XPS Pd spectrum contains two asymmetric doublets that can be assigned to 3d 5/2 and 3d 3/2 transitions, at lower and higher binding energies, respectively.…”
Section: Catalytic Activity Towards H 2 Productionmentioning
confidence: 99%
“…J o u r n a l P r e -p r o o f 6 Carbon black CD6008 employed as support for the catalysts preparation was provided by Columbian Chemicals Company (Brunswick, Ohio). Its specific surface area, determined by applying the Brunauer, Emmett and Teller (BET) method to the N2 adsorption isotherm at 77K, is 605 m 2 g -1 and the mesopore volume was 0.38 cm 3 g -1 [37].…”
Section: Reagents and Materialsmentioning
confidence: 99%
“…This method has been extended for a wide variety of metal nanoparticles to be used in a large number of applications (e.g. dehydrogenation of formic acid [37], oxygen reduction reaction [38] or sensing applications [39,40]). In fact, reduction of the metal catalyst in presence of the carbon material support has offered a good distribution of the nanoparticles onto the support with high reproducibility and loading.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have already reported that the dehydrogenation of FA (1) can be achieved under moderate reaction conditions upon the selection of a proper catalyst [10][11][12][13][14][15], while the reduction of CO2 to FA would be more challenging.…”
Section: Introductionmentioning
confidence: 99%